"Ah, eu acho a oralidade importantíssima!" A propósito da prática docente no ensino da oralidade - Débora Amorim Gomes da Costa Maciel; Maria Lúcia Ferreira de Figueirêdo Barbosa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
This paper is about a research with three teachers of elementary school, from municipal system of Recife's metropolitan region. We wanted to understand their knowledge about oral as a teaching object. We did a semi-structural interview and an individual one with all the subjects to explore their understanding about the objectives of teaching mother language, as well as rescue their practical elements and others. The data was treated in a qualitative view with content analysis bases in Bardin (1997). The results show us that the teachers understand the orality as one of the objectives of teaching mother language, despite their speech emphasizes reading, writing and language analysis. The results also show that there is a demand to what to teach. In general, it seems that they are not so clear about what is the working with the orality. However, the analyzed data offer methodological-teaching proposes that get fitted to explore the investigated pivot.